Supermarket business (Ann Arbor, Mich. : University Microfilms International, 1979)
'Profitable facts, trends, ideas, products for the grocery industry'.
Vol. 34-44 (1979-1989).
Includes index.
Formerly Supermarketing.
Requires the use of a microfiche reader.
Keywords: Grocery trade -- Periodicals; Supermarket -- Periodicals; Grocery trade